Crop genome‐wide association study: a harvest of biological relevance - Liu, Hai‐Jun; Yan, Jianbing (The Plant journal : for cell and molecular biology, 2019)
Summary With the advent of rapid genotyping and next‐generation sequencing technologies, genome‐wide association study (GWAS) has become a routine strategy for decoding genotype–phenotype associations in many species. More than 1000 such studies over the last decade have revealed substantial genotype–phenotype associations in crops and provided unparalleled opportunities to probe functional genomics. Beyond the many ‘hits’ obtained, this review summarizes recent efforts to increase our understanding of the genetic architecture of complex traits by focusing on non‐main effects including epistasis, pleiotropy, and phenotypic plasticity. We also discuss how these achievements and the remaining gaps in our knowledge will guide future studies. Synthetic association is highlighted as leading to false causality, which is prevalent but largely underestimated. Furthermore, validation evidence is appealing for future GWAS, especially in the context of emerging genome‐editing technologies. Significance Statement This review summarizes the latest advances in generating an overall view of the genetic architecture associated with crop complex traits, and discusses how these updated insights will guide future studies. A multiple‐causal‐allele hypothesis was formulated to explain the increasingly common artifact/synthetic associations.